Maya Anthropological Archaeology - Fisher, Chelsea R.; Chase, Arlen (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This volume examines the intersection between archaeologists working in the Maya area of Central American and local communities and agencies. It highlights issues of past colonial practice as well as issues involving modern tourism. The archaeologists involved in this volume attempt to suggest ways of bettering both community relationships and standards of practice for the field of Maya archaeology.